Pregnancy desire and dual method contraceptive use among people living with HIV attending clinical care in Kenya, Namibia and Tanzania. Issue 1 (14th December 2014) - Antelman, Gretchen; Medley, Amy; Mbatia, Redempta; Pals, Sherri; Arthur, Gilly; Haberlen, Sabina; Ackers, Marta; Elul, Batya; Parent, Julie; Rwebembera, Anath; Wanjiku, Lucy; Muraguri, Nicholas; et al.
Abstract : Aim: To describe factors associated with pregnancy desire and dual method use among people living with HIV in clinical care in sub-Saharan Africa. Design: Sexually active HIV-positive adults were enrolled in 18 HIV clinics in Kenya, Namibia and Tanzania. Demographic, clinical and reproductive health data were captured by interview and medical record abstraction. Correlates of desiring a pregnancy within the next 6 months, and dual method use [defined as consistent condom use together with a highly effective method of contraception (hormonal, intrauterine device (IUD), permanent)], among those not desiring pregnancy, were identified using logistic regression. Results: Among 3375 participants (median age 37 years, 42% male, 64% on antiretroviral treatment), 565 (17%) desired a pregnancy within the next 6 months. Of those with no short-term fertility desire ( n =2542), 686 (27%) reported dual method use, 250 (10%) highly effective contraceptive use only, 1332 (52%) condom use only, and 274 (11%) no protection. Respondents were more likely to desire a pregnancy if they were from Namibia and Tanzania, male, had a primary education, were married/cohabitating, and had fewer children. Factors associated with increased likelihood of dual method use included being female, being comfortable asking a partner to use a condom, and communication with a health care provider about family planning. Participants who perceived that their partner wanted a pregnancy were less likely to report dual method use. Conclusions: There was low dual method use and low use of highly effective contraception. Contraceptive protection was predominantly through condom-only use. These findings demonstrate the importance of integrating reproductive health services into routine HIV care.